How chief sustainability officers influence sustainability reporting : a study of Italian listed companies - Di Maio, Armando; Tyll, Ladislav; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates how the presence, hierarchical role, and competence of Chief Sustainability Officer (CSO) affect the quality and quantity of sustainability reporting among companies listed on Euronext Milan. Drawing on the Upper Echelons Theory and Legitimacy Theory, the study evaluates whether CSOs, especially those associated with top executive roles such as CEO or CFO, positively influence sustainability disclosure, assurance, and adherence to GRI standards. The findings reveal that CSO presence and expertise have a strong positive influence on sustainability reporting. However, mixed results are obtained when the CSO role is associated with the CEO or CFO, highlighting the complexity behind CSO appointment and the need for future research about sustainability leadership and reporting.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses